Reconstituição paleoclimática e paleoambiental em estuários com base no registo micropaleontológico de foraminíferos : relação com indicadores de escala local, regional e global - Moreno, João (2017)
Tese de doutoramento, Geologia (Paleontologia e Estratigrafia), Universidade de Lisboa, Faculdade de Ciências, 2017 In recent years, many studies have sought to produce high-quality paleoclimatic reconstructions for the late Holocene based on high-resolution (annual or decadal) biological and/or chemical proxies, both providing a great amount of information on climate variability and change over the last two millennia. In this context, salt marsh sedimentary records have previously proved to be particularly suitable in unravelling anthropogenic impacts on coastal ecosystems from those caused by climate variability and other natural stressors, at local and regional scales, with intertidal benthic foraminifera providing consistent responses to the latter, specifically to relative sea-level change. This dissertation focuses on showing evidence of climatic variability and change from a collection of multiple proxy studies combining marsh benthic foraminifera assemblages, wine production (WP), grape harvest dates (GHD), bromine (Br) contents in tidal marsh sediments, and different datasets ranging from the last decades, using instrumental (temperature–precipitation) records, to the past two millennia, by means of reconstructions (temperature, Total Solar Irradiance – TSI and North Atlantic Oscillation – NAO) and regional model (temperature–precipitation) simulations, with the aim of reconstruct the paleoclimate history of the west coast of Portugal for the past 2000 years. Simultaneously, the sensitivity of marsh benthic foraminifera to climate change induced by solar activity (SA) – via hydrological balance (controlling the salinity baseline of the high marsh environment) – is assessed, to show their reliability as a paleoclimatic proxy to be integrated in forthcoming studies. For that, the foraminiferal records from two dated sedimentary cores collected in the northwest (Caminha salt marsh; Minho River) and southwest (Casa Branca salt marsh; Mira River) Portuguese coast have been carefully examined and compared. ...